2016
DOI: 10.1002/2016jg003486
|View full text |Cite
|
Sign up to set email alerts
|

Snowpack fluxes of methane and carbon dioxide from high Arctic tundra

Abstract: Measurements of the land‐atmosphere exchange of the greenhouse gases methane (CH4) and carbon dioxide (CO2) in high Arctic tundra ecosystems are particularly difficult in the cold season, resulting in large uncertainty on flux magnitudes and their controlling factors during this long, frozen period. We conducted snowpack measurements of these gases at permafrost‐underlain wetland sites in Zackenberg Valley (NE Greenland, 74°N) and Adventdalen Valley (Svalbard, 78°N), both of which also feature automatic closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 74 publications
3
41
0
Order By: Relevance
“…In the recent work by Pirk et al (2016), the authors demonstrated that the fluxes of CH 4 1050 through the snowpack of permafrost Arctic wetlands during wintertime reflected a continuous emission of low amounts of gas still being produced in the soil, rather than solely the release of gas stored in the soil that was produced during the preceding growing season. These observations are in agreement with those from Mast et al (1998), where the authors reported evidence of microbial activity throughout winter in subalpine soils permitted by the insulat-1055 ing effect of the snow layer.…”
Section: Role Of Non-growing Season Ch 4 Emissionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the recent work by Pirk et al (2016), the authors demonstrated that the fluxes of CH 4 1050 through the snowpack of permafrost Arctic wetlands during wintertime reflected a continuous emission of low amounts of gas still being produced in the soil, rather than solely the release of gas stored in the soil that was produced during the preceding growing season. These observations are in agreement with those from Mast et al (1998), where the authors reported evidence of microbial activity throughout winter in subalpine soils permitted by the insulat-1055 ing effect of the snow layer.…”
Section: Role Of Non-growing Season Ch 4 Emissionsmentioning
confidence: 99%
“…and control the accumulation of gas, microbial activity, diffusion rates of gases, and the amount of oxygen in the soil (Sturtevant et al, 2012;Wickland et al, 1999;Pirk et al, 2016).…”
Section: Impact Of the Revised Model Structurementioning
confidence: 99%
See 3 more Smart Citations